Reactive oxygen species and sperm cells - Kurpisz Maciej; Sanocka Dorota (BMC, 2004)
Abstract There is a dynamic interplay between pro- and anti-oxidant substances in human ejaculate. Excessive reactive oxygen species (ROS) generation can overwhelm protective mechanism and initiate changes in lipid and/or protein layers of sperm plasma membranes. Additionally, changes in DNA can be induced. The essential steps of lipid peroxidation have been listed as well as antioxidant substances of semen. A variety of detection techniques of lipid peroxidation have been summarized together with the lipid components of sperm membranes that can be subjected to stress. It is unsolved, a threshold for ROS levels that may induce functional sperm ability or may lead to male infertility.